Pengaruh Laba, Arus Kas, dan Corporate Governance Terhadap Prediksi Financial Distress - Elvira Try Oktaviani; Mu'minatus Sholichah (JIATAX (Journal of Islamic Accounting and Tax), 2020)
This research aims to analyze the effect of earnings, cash flow, and corporate governance to predict financial distress. The Corporate governance in this study using the indicator frequency of board meeting, competence of audit committee, and institutional ownership. This research used annual report of the manufacturing companies listed on Indonesia Stock Exchange at the period of 2016-2018. The technique of selecting samples in this research uses purposive sampling and analyze data using logistic regression analysis. The result of this research showed that earnings and institutional ownership has an effect on the financial distress condition. While cash flow, frequency of board meeting, and competence of audit committee doesn’t has an effect on the financial distress condition.